What Does a Single-Item Measure of Job Stressfulness Assess? - Houdmont, Jonathan (Int J Environ Res Public Health, 2019)
Single-item measures of global job stressfulness are increasingly used in occupational health research, yet their construct validity remains unexplored. This study used a qualitative approach to identify frames of reference that underlie self-ratings on such a measure. Data were collected from a convenience sample of 55 adults in full-time employment who completed a single-item measure inviting a rating of the extent to which their job is generally stressful. A cognitive interview schedule was used to explore the factors taken into account when providing a global rating, with thematic analysis applied to identify themes in the interview transcripts. The most common frames of reference were the presence of problematic psychosocial working conditions, particularly job demands. Health characteristics, predominantly poor psychological wellbeing, emerged as a further less dominant secondary theme. Almost half the sample cited four or more referents. In terms of the timeframe under consideration, most participants referred to a long timeframe such as their work in general, with some specifying their current job and, a few, recent weeks. These findings shed light on the frames of reference used to inform judgements on global job stressfulness elicited by a single-item measure and in doing so contribute to the evidence base to support the application of such measures in occupational health research and organisational psychosocial risk management activities.